Simultaneous visualization of changes in perfusion and myocardial function of a transplanted heart in emergency cardiology - E. N. Ostroumov; E. V. Migunova; M. V. Vovchenko; G. A. Nefedova; A. A. Spasskiy; S. Yu. Shemakin; E. D. Kotina; K. S. Krupnova; L. T. Khamidova; A. A. Kanibolotskiy (Трансплантология (Москва), 2024)
Introduction. In conditions of the Emergency Cardiology Department, a timely and differential diagnosis of myocardial pathology is especially important in the absence of visible focal changes and significant coronary artery stenosis. This group of patients includes recipients of a transplanted heart, when it is difficult to count on the high sensitivity of perfusion images alone. This can be explained by the diffuse, balanced distribution of ischemia.Objective. To present the possibilities of perfusion myocardial single photon emission computed tomography synchronized with electrocardiography for a detailed assessment of the functional condition of both ventricles of the transplanted heartMaterial and methods. We have presented three clinical case reports of the patients with different pathology of the transplanted heart who referred themselves to the emergency cardiology clinic and underwent electrocardiographysynchronized perfusion myocardial single photon emission computed tomography for diagnostic purposes.Results. In all the cases presented, the radionuclide study influenced making the diagnosis and changing the treatment tactics. In the first case, it was possible to identify focal myocardial changes, for which coronary angiography and percutaneous coronary intervention with thromboextraction were immediately performed. In the second case, the image analysis reflecting the function of the myocardium (polar maps of wall movement and systolic thickening) allowed us to note a low efficacy of treatment for the transplanted heart rejection. In the third clinical case, the initial single photon emission computed tomography suggested the inflammatory nature of changes in the myocardium, which was verified by the results of endomyocardial biopsy.Conclusion. In the presented clinical cases, the urgently performed electrocardiography-synchronized perfusion myocardial single photon emission computed tomography made it possible to perform invasive interventions in time and thereby contribute to the recovery of the graft functional state and patient's condition improvement.